The Role of AI in Fostering Computational Thinking and Self-Efficacy in Educational Settings: A Systematic Review - Massaty, Muhammad Hassan; Fahrurozi, Slamet Kurniawan; Budiyanto, Cucuk Wawan (Universitas Sebelas Maret, 2024)
This systematic review explores the impact of artificial intelligence (AI) on the development of computational thinking and self-efficacy within educational environments. Computational thinking, a foundational skill in problem-solving, is increasingly recognized as essential for navigating a technology-driven world. AI tools and methodologies have been integrated into educational practices to enhance learning experiences and outcomes. This review synthesizes current literature to examine how AI technologies contribute to the cultivation of computational thinking skills among students of various ages and educational levels. Furthermore, it investigates the role of AI in bolstering students' self-efficacy confidence in one's ability to achieve goals in learning computational concepts. By analyzing empirical studies and educational interventions, this review identifies key mechanisms through which AI supports the development of these critical skills. Insights from this synthesis underscore the potential of AI to transform educational paradigms, providing opportunities for personalized learning, adaptive feedback, and collaborative problem-solving. The findings highlight implications for educators, policymakers, and researchers aiming to leverage AI effectively in educational settings to foster computational thinking and enhance students' self-efficacy, thereby preparing them for future challenges in a digital age.